“inventory is useless now but just to say”: The Politics of Ambivalence in Dionne Brand’s Land to Light On - Forster, Sophia (Studies in Canadian Literature, 2002)
Despite previous critical work that has suggested otherwise, ambivalence in Dionne Brand’s Land to Light On does infuse her views on language, identity, nation, and her sense of politics. Brand uses extensive inventories of contemporary and historical exploitations to describe a transnational network of oppressive power both impassive and impregnable, ultimately engaging in a side of identity politics neither its proponents nor its critics emphasize: the construction of the dominant oppressor against whom the recovered subject of oppression struggles. Land to Light On reflects Brand’s political ambivalence through the expression of a contradictory political project: the simultaneous construction and subversion of collective identity as a political strategy.